Early growth response gene-2 (Egr-2) regulates the development of B and T cells. - Suling Li; Alistair L J Symonds; Bo Zhu; Mengya Liu; Meera V Raymond; Tizong Miao; Ping Wang (PLoS ONE)
Background Understanding of how transcription factors are involved in lymphocyte development still remains a challenge. It has been shown that Egr-2 deficiency results in impaired NKT cell development and defective positive selection of T cells. Here we investigated the development of T, B and NKT cells in Egr-2 transgenic mice and the roles in the regulation of distinct stages of B and T cell development. Methods and findings The expression of Egr1, 2 and 3 were analysed at different stages of T and B cell development by RT-PCT and results showed that the expression was strictly regulated at different stages. Forced expression of Egr-2 in CD2(+) lymphocytes resulted in a severe reduction of CD4(+)CD8(+) (DP) cells in thymus and pro-B cells in bone marrow, which was associated with reduced expression of Notch1 in ISP thymocytes and Pax5 in pro-B cells, suggesting that retraction of Egr-2 at the ISP and pro-B cell stages is important for the activation of lineage differentiation programs. In contrast to reduction of DP and pro-B cells, Egr-2 enhanced the maturation of DP cells into single positive (SP) T and NKT cells in thymus, and immature B cells into mature B cells in bone marrow. Conclusions Our results demonstrate that Egr-2 expressed in restricted stages of lymphocyte development plays a dynamic, but similar role for the development of T, NKT and B cells.